Membangun Kesadaran Lingkungan Mahasiswa Melalui Mata Kuliah Keberlanjutan (Studi Kasus: Mahasiswa President University) - Yunita Ismail; Ronny Juwono; Dindin Dimyati; Johan Runtuk; Riyanto Adji (Jurnal Serambi Engineering, 2021)
This environmentally sound behavior is conveyed through giving courses on sustainability. The purpose of this study is to determine differences in environmental behavior, environmental imagine and environmental protection between students who receive courses on sustainability and students who do not. The method used is a quantitative method with data collection using a survey method through distributing questionnaires. The population used is students from the Faculty of Business as students who receive the subject of sustainability (in one subject, namely the Sustainability and Business subject) and students from the Engineering faculty (not from the Environmental Engineering study program), the computing faculty and the humanities faculty who do not get a special subject regarding sustainability. Samples were chosen deliberately with the criteria being President University students. The collected data were analyzed using the chi-square test to show significant differences regarding environmental behavior, environmental imagine and environmental protection. The results obtained indicate that there is no difference in environmental imagine and environmental protection between student that ever have sustainability subject and the student had not. In environmental behavior, several statements showed the differences and some not, such as witness burning rubbish, wasting of food, wasting of electricity and animal abuse.